Scatter my ashes at Bergdorf's [videorecording (DVD)] - Miele, Matthew; Miele, Matthew; Fichtner, William; Armani, Giorgio; Bergen, Candice, 1946-; Blahnik, Manolo, 1942-; Brown, Bobbi; Lagerfeld, Karl; Lucci, Susan; Olsen, Ashley, 1986-; Olsen, Mary-Kate, 1986-; Rivers, Joan; et al. (Entertainment One, 2013)
An anecdotal history of high-end Manhattan department store Bergdorf Goodman, as told by celebrities and icons of the fashion industry.